Estimating Fiscal Reaction Functions for Developing and Developed Countries: A Dynamic Panel Threshold Analysis - Turan, Taner; Iyidogan, Pelin Varol (Inst Economics Research Sas & Inst Forecasting Csps Sas, 2022)
Using a dynamic threshold regression method to estimate fiscal reaction functions, this paper examines the response of the primary surplus, government expenditure, and government revenue to the public debt for a large sample of countries over the period 2000 - 2018. Our empirical results lend a strong evidence for the dynamic threshold specification. Governments implement a sus-tainable fiscal policy until reaching the threshold level, but beyond this level the primary balance does not react to changes in public debt in developing coun-tries. On the other hand, for developed countries, primary balance gives a nega-tive (positive) response to an increase in the public debt when the debt is lower (higher) than the threshold level. Moreover, it seems that the primary balance is countercyclical. Besides the primary surplus, investigating the response of govern-ment expenditure and revenue provides valuable insights on the fiscal policy. Finally, dividing our sample as pre-and post-crisis periods we uncover some important changes in the fiscal policy after the last global financial crisis.
Keywords: dynamic threshold; reaction function; fiscal policy; sustainability; panel